Impact of partial fuel switch on household air pollutants in sub-Sahara Africa. (December 2017) - Tumwesige, Vianney; Okello, Gabriel; Semple, Sean; Smith, Jo
Abstract: Over 700 million people in Sub-Saharan Africa depend on solid biomass fuel and use simple cookstoves in poorly ventilated kitchens, which results in high indoor concentrations of household air pollutants. Switching from biomass to biogas as a cooking fuel can reduce airborne emissions of fine particulate matter (PM2.5 ) and carbon monoxide (CO), but households often only partially convert to biogas, continuing to use solid biomass fuels for part of their daily cooking needs. There is little evidence of the benefits of partial switching to biogas. This study monitored real-time PM2.5 and CO concentrations in 35 households in Cameroon and Uganda where biogas and firewood (or charcoal) were used. The 24 h mean PM2.5 concentrations in households that used: (1) firewood and charcoal; (2) both firewood (mean 54% cooking time) and biogas (mean 46% cooking time); and (3) only biogas, were 449 μg m −3, 173 μg m −3 and 18 μg m −3 respectively. The corresponding 24 h mean CO concentrations were 14.2 ppm, 2.7 ppm and 0.5 ppm. Concentrations of both PM2.5 and CO were high and exceeded the World Health Organisation guidelines when firewood and charcoal were used. Partially switching to biogas reduced CO exposure to below the World Health Organisation guidelines, but PM2.5 concentrations were only below the 24 h recommended limits when households fully converted to biogas fuel. These results indicate that partial switching from solid fuels to biogas is not sufficient and continues to produce concentrations of household air pollution that are likely to harm the health of those exposed. Programmes introducing biogas should aim to ensure that household energy needs can be fully achieved using biogas with no requirement to continue using solid fuels. Graphical abstract: Highlights: Air pollution exceeds WHO limits in African households using solid biomass fuels. A partial switch to biogas reduced CO concentrations to below the WHO limit. Particulates only fall to below the WHO limit with full conversion to biogas. Abstract : When households in Uganda and Cameroon partially switched to biogas, the carbon monoxide exposure was reduced to below the World Health Organisation air quality guidelines, but concentrations of particulate matter with an aerodynamic diameter of 2.5 μm remained above guidance values and only fell below these when household fuel conversion to biogas was complete.